Influence of glycoprotein MUC1 on trafficking of the Ca2+-selective ion channels, TRPV5 and TRPV6, and on in vivo calcium homeostasis - Al-Bataineh, Mohammad M; Kinlough, Carol L; Marciszyn, Allison; Lam, Tracey; Ye, Lorena; Kidd, Kendrah; Maggiore, Joseph C; Poland, Paul A; Kmoch, Stanislav; Bleyer, Anthony; Bain, Daniel J; Montalbetti, Nicolas; et al. (The Journal of biological chemistry, 2023)
Polymorphism of the gene encoding mucin 1 (MUC1) is associated with skeletal and dental phenotypes in human genomic studies. Animals lacking MUC1 exhibit mild reduction in bone density. These phenotypes could be a consequence of modulation of bodily Ca homeostasis by MUC1, as suggested by the previous observation that MUC1 enhances cell surface expression of the Ca2+-selective channel, TRPV5, in cultured unpolarized cells. Using biotinylation of cell surface proteins, we asked whether MUC1 influences endocytosis of TRPV5 and another Ca2+-selective TRP channel, TRPV6, in cultured polarized epithelial cells. Our results indicate that MUC1 reduces endocytosis of both channels, enhancing cell surface expression. Further, we found that mice lacking MUC1 lose apical localization of TRPV5 and TRPV6 in the renal tubular and duodenal epithelium. Females, but not males, lacking MUC1 exhibit reduced blood Ca2+. However, mice lacking MUC1 exhibited no differences in basal urinary Ca excretion or Ca retention in response to PTH receptor signaling, suggesting compensation by transport mechanisms independent of TRPV5 and TRPV6. Finally, humans with autosomal dominant tubulointerstitial kidney disease due to frame-shift mutation of MUC1 (ADTKD-MUC1) exhibit reduced plasma Ca concentrations compared to control individuals with mutations in the gene encoding uromodulin (ADTKD-UMOD), consistent with MUC1 haploinsufficiency causing reduced bodily Ca2+. In summary, our results provide further insight into the role of MUC1 in Ca2+-selective TRP channel endocytosis and the overall effects on Ca concentrations.
Keywords: TRPV Cation Channels; Calcium; mutace; epitelové buňky; vápník; sexuální faktory; Mucin-1; Epithelial Cells; kultivované buňky; Cell Membrane; Animals; lidé; ženské pohlaví; Humans; zvířata; Sex Factors; buněčná membrána; myši; mucin 1; Protein Transport; Cells, Cultured; Mutation; Mice; kationtové kanály TRPV; Female; transport proteinů